2022
DOI: 10.3390/nano12122108
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin Ultrafine Powder Was Prepared by a New Anti-Solvent Recrystallization Method

Abstract: Raw naringenin directly isolated from plants is significantly limited by its poor dissolution rate and low bioavailability for clinical and in vivo studies. This study reported a method for the preparation of naringenin ultrafine powder (NUP) using a novel anti-solvent recrystallization process; preliminary experiments were conducted using six single-factor experiments. The response surface Box–Behnken (BBD) design was used to optimize the level of factors. The optimal preparation conditions of the DMP were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This method typically involves dissolving the target substance in a solvent and then adding an anti-solvent that mixes well with the solvent but has a lower solubility for the target substance. By controlling the amount of anti-solvent added, the solubility of the target substance in the solution is reduced, prompting it to recrystallize [35,36]. Antisolvent recrystallization can be used to separate and purify taxanes from crude extracts of T. mairei, with the best purification effect achieved using methanol as the solvent and water as the anti-solvent.…”
Section: Examples Of Liquid Extractions From Taxusmentioning
confidence: 99%
“…This method typically involves dissolving the target substance in a solvent and then adding an anti-solvent that mixes well with the solvent but has a lower solubility for the target substance. By controlling the amount of anti-solvent added, the solubility of the target substance in the solution is reduced, prompting it to recrystallize [35,36]. Antisolvent recrystallization can be used to separate and purify taxanes from crude extracts of T. mairei, with the best purification effect achieved using methanol as the solvent and water as the anti-solvent.…”
Section: Examples Of Liquid Extractions From Taxusmentioning
confidence: 99%
“…Naringenin (4, 5, 7‐trihydroxyflavone) is a flavonoid compound found in plants and abundant in citrus fruits 29,30 . It was confirmed that Naringenin has a variety of pharmacological activities, such as anti‐inflammatory, antioxidant, antitumor, immune regulation, and so forth 31–34 .…”
Section: Introductionmentioning
confidence: 96%
“…Naringenin (4, 5, 7-trihydroxyflavone) is a flavonoid compound found in plants and abundant in citrus fruits. 29,30 It was confirmed that Naringenin has a variety of pharmacological activities, such as anti-inflammatory, antioxidant, antitumor, immune regulation, and so forth. [31][32][33][34] While previous studies have reported the anti-RA effects of Naringenin and Naringin, these studies have focused mainly on their in vivo effects and modulation of dendritic cell function, lacking a comprehensive exploration of the anti-inflammatory mechanism of Naringenin.…”
Section: Introductionmentioning
confidence: 98%